Implementation of the Inquiring Minds Want to Know Model in Increasing Student Learning Activity - Ariqa, Fathia Fitri; Widda, Widda; Nasbi, Khairun; Medianto, Rivo; Puadah, Popi (Journal International of Lingua and Technology, 2025)
Student learning engagement is a key indicator of a successful learning process. In practice, many teachers still use conventional methods that tend to make students passive, simply receiving material without responding critically. The Inquiring Minds Want to Know model presents itself as an innovative learning approach that positions student curiosity as the primary driver of learning activities. This model encourages students to actively ask questions, gather information, and find answers through exploration. Various literature shows that implementing this model can increase student participation, critical thinking skills, and learning motivation. Therefore, this study was conducted to examine the implementation of this model through a review of relevant literature. This study aims to describe how the implementation of the Inquiring Minds Want to Know model can improve student learning engagement. Furthermore, it also aims to identify factors contributing to the model's successful implementation and challenges teachers may face in the classroom. This research employed a qualitative method with a literature review approach. Data were obtained from various journals, articles, and previous research relevant to the topic. Analysis was conducted by reviewing, organizing, and summarizing the literature findings related to the implementation of the Inquiring Minds Want to Know model. The literature review results indicate that this model effectively increases student learning engagement. Students are more confident in expressing opinions, asking questions, and actively participating in discussions. The teacher acts as a facilitator, stimulating students' curiosity through open-ended questions and contextual problems. The study concluded that implementing the Inquiring Minds Want to Know model had a positive impact on student learning engagement. This model can be a solution for teachers to create an interactive, critical, and enjoyable learning environment.